2016
DOI: 10.1038/srep27541
|View full text |Cite
|
Sign up to set email alerts
|

Reversing diet-induced metabolic dysregulation by diet switching leads to altered hepatic de novo lipogenesis and glycerolipid synthesis

Abstract: In humans, low-energy diets rapidly reduce hepatic fat and improve/normalise glycemic control. Due to difficulties in obtaining human liver, little is known about changes to the lipid species and pathway fluxes that occur under these conditions. Using a combination of stable isotope, and targeted metabolomic approaches we investigated the acute (7–9 days) hepatic effects of switching high-fat high-sucrose diet (HFD) fed obese mice back to a chow diet. Upon the switch, energy intake was reduced, resulting in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
4
18
0
Order By: Relevance
“…We found that glucose tolerance was compromised within 1 week of HFD60 feeding, in good agreement with several studies evaluating short-term effects of HFD feeding [3,8,[28][29][30]. It was previously shown that glucose intolerance induced by an approximately 9-week HFD-feeding protocol can be restored within 1 week by switching to a control diet [31]. Our study now demonstrates that even after longer periods of exposure to an HFD, glucose tolerance is promptly reasserted in response to a reduction in dietary fat intake.…”
Section: Discussionsupporting
confidence: 91%
“…We found that glucose tolerance was compromised within 1 week of HFD60 feeding, in good agreement with several studies evaluating short-term effects of HFD feeding [3,8,[28][29][30]. It was previously shown that glucose intolerance induced by an approximately 9-week HFD-feeding protocol can be restored within 1 week by switching to a control diet [31]. Our study now demonstrates that even after longer periods of exposure to an HFD, glucose tolerance is promptly reasserted in response to a reduction in dietary fat intake.…”
Section: Discussionsupporting
confidence: 91%
“…17 The current data suggest that in body weight-stable individuals with NAFLD, an increased supply of acetate to the liver from the colonic fermentation of inulin provides surplus acetyl-CoA for DNL and hepatic lipid accretion. Interestingly, diet-induced body weight loss in mice has been shown to markedly reduce insulin levels and rates of hepatic DNL, 19 whilst the expression of hepatic DNL-related genes is also reduced by states of chronic negative energy balance. 20 This may explain the disparate effect of inulin supplementation on liver fat content in the current study compared with our previous investigation when inulin intervention was added to a hypocaloric diet that achieved a~5% reduction in body weight.…”
Section: Resultsmentioning
confidence: 99%
“…2,[4][5][6][7][8][9] Conversely, removal of HFD was shown to reverse most of these changes. 2,10,11 For some time it was believed, that the total number of fat cells is set during adolescence and a change of fat mass in adults is exclusively caused by hypertrophy. 12,13 However, it was recently demonstrated that hyperplasia plays an important role in obesity and that the ability for an increase in adipocyte number persists for lifetime even after severe weight loss.…”
Section: Introductionmentioning
confidence: 99%